2014
DOI: 10.26477/idj.v36i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Oral Mucositis in Children Suffering from Acute Lymphoblastic Leukaemia”

Abstract: Background: Oral mucositis is the most commonly reported side effect observed in neoplastic patients treated with chemotherapy and radiotherapy of the head and neck region as well as in patients who have received a haematopoietic stem cell transplant. The aim of the study was to assess the oral mucosa status in children with acute lymphoblastic leukaemia (ALL) during antineoplastic therapy. Material and methods:The clinical examination included 127 children aged 5-15 with ALL. The clinical examination was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
1
1
2
Order By: Relevance
“…In the pediatric group, the male gender was observed more than females and this is in agreement with Iraqi studies by Al-Hadad et al (23) , Shalal et al (26) , Mustafa et al (27) , and Alani et al (28) as well as other studies by Liu et al (17) , Mosaad et al (19) , Hussein et al (24) , and Ali et al (25) .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the pediatric group, the male gender was observed more than females and this is in agreement with Iraqi studies by Al-Hadad et al (23) , Shalal et al (26) , Mustafa et al (27) , and Alani et al (28) as well as other studies by Liu et al (17) , Mosaad et al (19) , Hussein et al (24) , and Ali et al (25) .…”
Section: Discussionsupporting
confidence: 89%
“…Bleeding tendency and splenomegaly were the most common presenting complaints in the pediatric group included and this following the Eygptian study by Mosaad et al (19) , but was different from the result of the Iraqi study by Shalal et al (26) who reported that most frequent symptoms were fever and pallor and another Iraqi study by Alani, (28) which show that swollen lymph node was the most presenting symptom.…”
Section: Discussioncontrasting
confidence: 54%
“…Another proposed mechanism is that repair of the mucosa is accelerated with the recovery of white cells and neutrophil counts. 12 The present study found no association between platelet counts and oral mucositis. This disagrees with the results of Mendonça et al from Brazil and Ye et al from Sweden, who found a highly significant association.…”
Section: Table 3 Severity Of Oral Mucositis By Type Of Cancercontrasting
confidence: 71%
“…9 However, according to Devaraju et al from India, the leukocyte levels below 2,500/μL increase the risk of oral mucositis. 10 The probable reason for the finding of 5,[11][12][13] The possible factors for the link between ANC count and severity of oral mucositis rose from the topical and systemic GM-CSF treatment that reduced duration and severity of oral mucositis by recovering neutrophil counts. 11 Predisposition to mucositis is high in patients with low neutrophil counts (<500 cell/μL) because the incidence of microbial infection increased.…”
Section: Table 3 Severity Of Oral Mucositis By Type Of Cancermentioning
confidence: 99%